PENERAPAN METODE BERMAIN DAN BERLOMBA UNTUK MENINGKATKAN HASIL BELAJAR PJOK PADA MATERI ATLETIK SISWA KELAS IX.B SMPN 1 BANGKINANG SEBERANG T.P 2018/2019 - PATUA BUJANG (STKIP ROKANIA, 2019)
The objectives of this study are student learningoutcomes through the Application of Learning byplaying and competing. This research is a ClassroomAction Research (CAR) which is carried out within thecycle. Each cycle consists of four steps: namely,planning, action, observation, and reflection. Thesubject of this study was class IX.B SMP Negeri1Bangkinang Seberang with the number of students 25person. To get data in this study, researchers used twoinstruments, namely observation sheet activity, skillsand results of the PJOK test from students. Studentactivities for each indicator are given and analyzedusing percentage techniques. Improved learningoutcomes can be seen from the number of students whocomplete the KKM set by the school. Results researchThe application of the game method and competing toimprove PJOK learning outcomes in athletic materialfor class IX.B students of SMP Negeri 1 BangkinangSeberang can be summarized as follows: Percentage ofcompleteness of students after learning the method ofthe game and competing based on the value ofknowledge has increased from 56% in the previous UHto 76% in the first cycle and 92% in the second cycle.Activity values increased from 60% in previouslearning to 96 at meeting 1, 100% at meeting 2, and96% at meetings 1 and 2 of cycle II. Learning outcomesof students' skills increased from 60% before the cycle to 80% in the first cycle and 92% in the second cycle.